Axial mechanical properties of welded orthogonal trapezoidal aluminum honeycomb as filler material for nuclear equipment impact limiter - Youdong Xing; Baixing Deng; Tianwei Qiu; Mengzhen Cao; Yukun An; Ertuan Zhao; Siyi Yang (Scientific Reports)
Abstract Lightweight porous structural materials have excellent energy absorption performance, and their application are gradually appeared. This paper takes the shock-absorbing material of nuclear equipment transportation casks as the starting point, and manufactures an orthogonal trapezoidal aluminum honeycomb by welding (WOTAH). The mechanical properties with different cell thicknesses and cell size ratios under different impact loads are studied through experimental and simulation methods, and the deformation process and energy absorption performance of the materials are obtained. The energy absorption performance of materials under quasi-static loading was investigated using plastic deformation theory and compared with experimental results. Based on the experimental results, the least squares method was used for data fitting to obtain the C-S dynamic constitutive relationship of the material. The equivalent structure was used to replace the honeycomb structure for simulation, and the influence of strain rate effect and structural size on material properties was further studied. Through the above mechanical performance analysis and comparison with wood, it is shown that WOTHA has feasible for the application of nuclear equipment impact limiter.